Retinal toxicity of intravitreal tenecteplase in the rabbit - Rowley, S A (Copyright 2004 British Journal of Ophthalmology, 2004)
Aim: To investigate the retinal toxicity of intravitreal injection of a novel fibrinolytic tenecteplase in rabbit eyes. Methods: Tenecteplase (25–350 μg in 0.1 ml BSS) was injected into the vitreous cavity of normal rabbit eyes. Control (fellow) eyes received 0.1 ml of BSS. One day, 1 week, and 2 months post-injection, the eyes were examined by slit lamp biomicroscopy, indirect ophthalmoscopy, and electroretinography, and then harvested for histopathological examination. Results: No evidence of retinal toxicity was seen with tenecteplase doses up to and including 50 μg. At a dose of 150 μg ophthalmoscopy was normal, but histology showed mild retinal damage in the inner nuclear layer and electroretinography showed a temporary reduction in B-wave amplitude. At doses of 200 μg and above, there was evidence of retinal toxicity on electroretinography, ophthalmoscopy, and histology. Ophthalmoscopic findings included vitreal fibrosis, retinal necrosis and tractional retinal detachment and light microscopy revealed necrosis of retinal pigment epithelium and other retinal layers. Damage was centred around the injection site but was more widespread with the higher doses. Conclusion: A dose of 50 μg tenecteplase appears safe for intravitreal injection in the rabbit. Tenecteplase could have potential applications in the treatment of submacular haemorrhage and retinal vein occlusion.